Inside the skin of a patient with diabetes: fostering cognitive empathy through insulin pump simulation - Ryan, Paul (Canadian Medical Education Journal, 2020)
Implication Statement In order to best treat a patient, the carer must be able to clearly see their point of view. In the case of the complexities of insulin pump therapy, physicians may not fully understand the common challenges that drive patients to non-adherence. The author undertook a three-day simulation using wearable technology to explore this experience. This form of simulation represents a simple yet effective means by which to foster cognitive empathy in undergraduate and postgraduate medical education settings alike.